2016
DOI: 10.1073/pnas.1523580113
|View full text |Cite|
|
Sign up to set email alerts
|

Root exudates drive interspecific facilitation by enhancing nodulation and N 2 fixation

Abstract: Plant diversity in experimental systems often enhances ecosystem productivity, but the mechanisms causing this overyielding are only partly understood. Intercropping faba beans (Vicia faba L.) and maize (Zea mays L.) result in overyielding and also, enhanced nodulation by faba beans. By using permeable and impermeable root barriers in a 2-y field experiment, we show that root-root interactions between faba bean and maize significantly increase both nodulation and symbiotic N 2 fixation in intercropped faba bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
191
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 335 publications
(216 citation statements)
references
References 42 publications
17
191
0
8
Order By: Relevance
“…intercropping systems (Li et al 2007(Li et al , 2014. Positive plant-plant interactions, such as root-root facilitation, have been shown to play a significant role for P acquisition (Li et al 2007;Brooker et al 2015;Li et al 2016;Zhang et al 2016). Tang et al (2016) further demonstrated the greater performance of such intercropping systems compared to single crop systems under field conditions along a P fertility gradient.…”
Section: Nutrient Acquisition and Nutrient Cyclingmentioning
confidence: 97%
See 2 more Smart Citations
“…intercropping systems (Li et al 2007(Li et al , 2014. Positive plant-plant interactions, such as root-root facilitation, have been shown to play a significant role for P acquisition (Li et al 2007;Brooker et al 2015;Li et al 2016;Zhang et al 2016). Tang et al (2016) further demonstrated the greater performance of such intercropping systems compared to single crop systems under field conditions along a P fertility gradient.…”
Section: Nutrient Acquisition and Nutrient Cyclingmentioning
confidence: 97%
“…Through their nutritive effects, exudates will affect the structure of soil microbial communities, favoring cell division of bacteria able to catabolize them. Though microbe-plant chemical dialogues are well-known in the case of symbiotic interactions between legumes and nitrogen-fixing rhizobia (Limpens et al 2015;Li et al 2016) or in plant mycorrhiza (Parniske 2008), these are less well characterized in plant-PGPR interactions.…”
Section: Communication In the Rhizospherementioning
confidence: 99%
See 1 more Smart Citation
“…These genes play a critical role in different biological processes associated with NUE such as uptake, assimilation, and utilization efficiency (Han et al, 2016). Early nodulation 93 (ENOD93) gene play a significant role in cell wall reorganization during nodulation in legumes (Li et al, 2016). ENOD93 is an active member of early nodulin-like proteins family.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of OsENOD93-1 in transgenic rice plant increased the shoot dry biomass and seed yield. Li et al, (2016) suggested that ENOD93 gene showed up-regulation and promoted nitrogen fixation in faba beans. Despite the critical interplay of ENOD93-1 gene in N regulation, no efforts were made in past to identify ENOD93-1 gene in wheat.…”
Section: Introductionmentioning
confidence: 99%